Upregulation of AT1 Receptor Mediates a Pressor Effect Through ROS-SAPK/JNK Signaling in Glutamatergic Neurons of Rostral Ventrolateral Medulla in Rats With Stress-Induced Hypertension - Jiang, Liping; Zhou, Xuan; Yang, Hongyu; Guan, Ruijuan; Xin, Yanlei; Wang, Jijiang; Shen, Linlin; Zhu, Danian; Ma, Shulan; Wang, Jin (Frontiers in Physiology, 2019)
The present study examined whether angiotensin II (Ang II) mediates the pressor effect through nicotinamide adenine dinucleotide phosphate (NADPH) oxidase-derived reactive oxygen species (ROS)-mitogen-activated protein kinase (MAPK) signaling in the glutamatergic neurons of the rostral ventrolateral medulla (RVLM) in stress-induced hypertensive rats (SIHR). The SIHR model was established using electric foot-shocks combined with noises for 15 days. We observed that Ang II type 1 receptor (AT1R) and the glutamatergic neurons co-localized in the RVLM of SIHR. Furthermore, glutamate levels in the intermediolateral column of the spinal cord were higher in SIHR than in controls. Microinjection of Ang II into the RVLM of SIHR activated stress-activated protein kinase/Jun N-terminal kinase (SAPK/JNK), extracellular signal-regulated protein kinase (ERK) 1/2, and p38MAPK. Compared with controls, the activation of SAPK/JNK, ERK1/2, p38MAPK, and ROS in the RVLM were higher in SIHR, an effect that was blocked by an NADPH oxidase inhibitor (apocynin) and an AT1R antagonist (candesartan). RVLM microinjection of apocynin or a SAPK/JNK inhibitor (SP600125), but not an ERK1/2 inhibitor (U0126) or a p38MAPK inhibitor (SB203580), decreased AT1R mRNA and mean arterial blood pressure (MABP) in SIHR. The increase of AT1R protein expression and mean arterial blood pressure (MABP) was inhibited by intracerebroventricular infusion, for 14 days, of a SAPK/JNK inhibitor (SP600125), but not an ERK1/2 inhibitor (U0126) or a p38MAPK inhibitor (SB203580) in SIHR. RVLM microinjection of apocynin or SP600125, but not U0126 or SB203580, decreased MABP in SIHR. We conclude that Ang II modulates the pressor effect through AT1R-dependent ROS-SAPK/JNK signaling in glutamatergic neurons in the RVLM of SIHR.